Correction: Ramadan fasting and weight change trajectories: Time-varying association of weight during and after Ramadan in low-income and refugee populations. - Daniel E Zoughbie; Tin Lok James Ng; Jacqueline Y Thompson; Kathleen T Watson; Rami Farraj; Eric L Ding (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pgph.0000371.].